The Smartphone as a Pedagogic Tool. Student Profiles as related to its Use and Knowledge - Irina Salcines-Talledo; Natalia González-Fernández; Elena Briones (Springer, 2020)
The Smartphone has become the device that offers the greatest number of possibilities to Mobile Learning dynamics, and university students are increasingly optimizing its potential. This research offers a classification of student profiles according to their knowledge and use of Smartphones, and analyzes their relationship between their interest towards training, the perceived academic benefits and the time spent using the device as a pedagogic resource. For this, through a quantitative methodology, a cluster analysis was conducted, which allowed for the defining of student profiles, and through non-parametric tests, the significance was analyzed with respect to their interest in training, the academic benefits perceived, and the time spent using the Smartphone. The results showed the existence of three profiles, namely: High degree of knowledge and academic use of the Smartphone; Average degree of knowledge and use of the Smartphone; and Low degree of knowledge and use of the Smartphone. Also, differences between the profiles were found in the time spent using it, the benefits perceived and the interest for being trained on the academic use of the Smartphone. The students with the Low profile were the ones that detected the least number of positive aspects and had the least interest in training towards this aim.